Urolithin A alleviates advanced glycation end-product formation by altering protein structures, trapping methylglyoxal and forming complexes. Issue 23 (4th November 2021) - Peng, Chun-yan; Zhu, Hua-dong; Zhang, Lu; Li, Xiao-feng; Zhou, Wen-na; Tu, Zong-cai
Abstract : UroA alleviated AGEs formation in HSA–fructose system by changing HSA structure, trapping reactive MGO, forming UroA–HSA complexes, and altering the glycation activity of Lys residues. Abstract : Urolithin A (UroA) is a first-in-class natural compound derived from the gut microbiota-derived metabolites of ellagitannins. This research for the first time evaluates the mechanisms of UroA inhibiting advanced glycation end-product (AGE) formation by fluorescence spectroscopy, molecular docking, liquid chromatography (LC) and LC-Oribitrap tandem mass spectrometry. The results indicated that UroA exhibited a good suppression effect on the formation of AGEs in human serum albumin (HSA)–fructose and HSA–methylglyoxal (MGO) systems. Further mechanism analysis revealed that UroA alleviated AGE formation by changing the conformational structure of HSA, trapping reactive MGO to form mono-MGO–UroA complexes, promoting the exposure of chromophores to a more hydrophobic micro-environment, and forming stable UroA–HSA complexes. UroA bound with HSA in an equimolar manner, the binding was an exothermic spontaneous process, subdomain IIIA was the preferred binding pocket, and hydrogen bonding, hydrophobic interactions and van der Waals forces were the major interaction forces. The number of glycation sites detected in glycated HSA was reduced by 1 and 2, respectively, when 181.82 and 363.64 μM UroA was added. These could provide an insight into the mechanism of UroA inhibiting HSA glycation, and highlight its value as a promising glycation inhibitor in the prevention of diabetic complications.